2006
DOI: 10.1158/0008-5472.can-06-0576
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of the Tumor Suppressor Cystatin M Occurs during Breast Cancer Progression

Abstract: Cystatin M is a secreted inhibitor of lysosomal cysteine proteases. Several lines of evidence indicate that cystatin M is a tumor suppressor important in breast malignancy; however, the mechanism(s) that leads to inactivation of cystatin M during cancer progression is unknown. Inspection of the human cystatin M locus uncovered a large and dense CpG island within the 5 ¶ region of this gene (termed CST6). Analysis of cultured human breast tumor lines indicated that cystatin M expression is either undetectable o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 49 publications
9
84
0
Order By: Relevance
“…In a subsequent study, methylation analysis of CST6 in breast cancer cell lines revealed an inverse correlation between CpG island hypermethylation and CST6 gene expression, and the extent of regional methylation in the proximal promoter was strongly correlated with the lack of CST6 expression (Rivenbark et al, 2006a). Consistent with these findings, several other studies have shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006).…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…In a subsequent study, methylation analysis of CST6 in breast cancer cell lines revealed an inverse correlation between CpG island hypermethylation and CST6 gene expression, and the extent of regional methylation in the proximal promoter was strongly correlated with the lack of CST6 expression (Rivenbark et al, 2006a). Consistent with these findings, several other studies have shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006).…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, expression of CST6 in MDA-MB-435S breast cancer cells delays tumorigenesis by transplanted cells and suppresses spontaneous formation of liver and lung metastases (Zhang et al, 2004). More recently, it has been shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines (Ai et al, 2006;Rivenbark et al, 2006a;Schagdarsurengin et al, 2006;Shridhar et al, 2004) and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006). Ai et al showed that 12/20 (60%) primary breast tumors exhibit CST6 promoter hypermethylation, and microdissection of individual cells from select tumors revealed that methylation occurs in both DCIS and IDC cells (Ai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations